“Contemporary Art, the Market, and the Global South” (submitted) - Conde, I. (The TIAMSA International Conference, The Art Market and the Global South: New Perspectives and Plural Approaches, IHA / FCSH/ Universidade Nova, Lisbon, 21 – 22 November, 2019 (TIAMSA – The International Art Market Studies Association), 2019)
Abstract: Coming from a study the recognition of contemporary art, e.g. issues, processes, mediations, and elites, now updated with a section with European and international scope, this paper gathers a two fold perspective in which the main is the notion of value(s). Beyond floating and multidimensional meanings, the paper for a conference on the art market and the Global South adopts a rather pagmatic outlook, at first to frame “value chains” as they operate in the ground. A mapping from the latest study for the European Commission on cultural and creative sectors, updating their cartography by the inclusion of digitisation an overall axis. Besides the pertinent chapter on the visual arts, it matters the reference to the EU and Europe at large because of a part that belongs to the called Global South – and, so, where is it in the international market for the contemporary art? Here comes the second fold of my perspective with empirical appraisal not of the financial flows but of the position of the artists in some rankings, supposedly representative of geographies, reputational capital, and market value. Moreover, who rises to the vertex? For instance, the narrow elite of the first 150 positions (30%) in the “Top 500 contemporary artists”, as listed by artprice.com in the 2018 Report. In such elite the Global South is mainly represented by Asia (39.4%) with Chinese monopoly (33.3%), in contrast to the tiny fraction for Latin America (2%) and others (Australia, South Africa, Iran: 2.7%). The USA corresponds to around 31%, and Europe to 26%, although its Southern artists only amount to 4.7%, from countries like Spain, Italy, Romenia, and adding France (with 2%) due to a part of the country in the South Europe. In any case, quite below Germany (10%) and UK (8.7%). Complementary analysis shows an older market elite (around 72% aged above 50 years) and few 11 women. Anyway, from different generations and four of them related to the Global South: since Beatriz Milhazes and Adriana Varejão from Brazil, to the Chinese MI Qiaoming and the South African painter Marlene Dumas nevertheless currently based in Amsterdam. Besides this elite, the presentation enlarges the portrait to the 500 top artists, parallel to data from other sources and also beyond the commercial market to achieve a comparative outlook including examples from institutional and informal systems in the wide space of contemporary art. With which distinctions, portraits, values and elites?